(untitled) (Journal of Economic Research & Business Administration, 2021)
Project management is a prerequisite for the company’s sustainable development. The pandemic caused great damage to the hospitality industry, so hotels began to develop separate projects to implement anti-crisis measures. Project management is not only a tool for achieving business goals, but also a mechanism for the strategic development of the company. This is due to the fact that the achievement of strategic goals in any area is directly related to the effective implementation of individual projects. The purpose of this study is to substantiate the importance of project management as one of the directions of anti-crisis measures of the hotel business in the context of a pandemic, to determine the level of maturity of project management and to form the practice of project management in the activities of Kazakhstani hotels. The article considers the activities of hotels in the southern regions of the Republic of Kazakhstan. The results of the study showed that the experience of project management in hotels has not yet been formed, respectively, the success of implemented projects in risk conditions is reduced, so there is a need to introduce a project management maturity model as an evaluation tool. The most frequently used tool in the hotel business is the holding of morning meetings and meetings, and the identification of risks was in the last place. The tools of the planning process group are of paramount importance in this industry. The selected tools are combined into project management process groups and a project management practice for the hospitality industry has been developed. Key words: project management, hotel business, pandemic.